Statins change the cytokine profile in Trypanosoma cruzi-infected U937 macrophages and murine cardiac tissue through Rho-associated kinases inhibition - González-Herrera, Fabiola; Clayton, Natasha S.; Guzmán-Rivera, Daniela; Carrillo, Ileana; Castillo, Christian; Catalán, Mabel; Anfossi, Renatto; Quintero-Pertuz, Helena; Quilaqueo, María Elena; Olea-Azar, Claudio; Rivera-Meza, Mario; Kemmerling, Ulrike; et al. (Frontiers in Immunology, 2023)
Chronic Chagasic cardiomyopathy (CCC), caused by the protozoan Trypanosoma cruzi, is the most severe manifestation of Chagas disease. CCC is characterized by cardiac inflammation and fibrosis caused by a persistent inflammatory response. Following infection, macrophages secrete inflammatory mediators such as IL-1β, IL-6, and TNF-α to control parasitemia. Although this response kills the parasites, it causes damage to the heart tissue. Thus, the use of immunomodulators is a rational alternative to CCC. Rho kinase (ROCK) 1 and 2 are RhoA-activated serine/threonine kinases that regulate the actomyosin cytoskeleton. Both ROCKs have been implicated in the polarization of macrophages towards an M1 (proinflammatory) phenotype. Statins are FDA-approved lipid-lowering drugs that reduce RhoA signaling by inhibiting geranylgeranyl pyrophosphate (GGPP) synthesis. In this study, we demonstrate for the first time in macrophages that incubation with T. cruzi leads to ROCK activation via the TLR4 pathway, which triggers NF-κB activation. Inhibition of ROCKs by Y-27632 prevents the expression and secretion of M1 markers, as does treatment with atorvastatin. Furthermore, we show that the effect of atorvastatin on the NF-kB pathway and cytokine secretion is mediated by ROCK. Finally, statin treatment decreased ROCK expression and proinflammatory cytokine production, promoting antiinflammatory cytokine expression in chronic chagasic mice hearts. These results suggest that the statin modulation of the inflammatory response due to ROCK inhibition is a potential pharmacological strategy to prevent cardiac inflammation in CCC.